1993
DOI: 10.1259/0007-1285-66-788-714
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray fluorescence system for the determination of gold in vivo following chrysotherapy

Abstract: This paper describes a low cost mobile measurement system for the determination of gold in vivo base around a 153Gd radiation source and a hyper pure germanium detector. Early clinical results are also presented to demonstrate the efficacy of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Furthermore, a number of in vivo studies of toxic elements that accumulate in human bone have been reported, such as uranium, 13 mercury, 14 and gold. 15 XRF was successfully applied for the measurement of platinum 16,17 as well. The most recognized and applied XRF technique, nevertheless, is bone lead XRF measurements in humans.…”
Section: The Basic Components Of a Soft X-ray Fluorescence Systemmentioning
confidence: 99%
“…Furthermore, a number of in vivo studies of toxic elements that accumulate in human bone have been reported, such as uranium, 13 mercury, 14 and gold. 15 XRF was successfully applied for the measurement of platinum 16,17 as well. The most recognized and applied XRF technique, nevertheless, is bone lead XRF measurements in humans.…”
Section: The Basic Components Of a Soft X-ray Fluorescence Systemmentioning
confidence: 99%
“…Furthermore, a number of in vivo studies of toxic elements that accumulate in human bone and joints have been reported such as uranium, 5 mercury, 6 and gold. 7 XRF was successfully applied for measurement of platinum 8,9 and bismuth 3 as well.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, in vivo applications have been developed for measurements of cadmium, mercury, gold, platinum, uranium and a number of other elements through the years (Christoffersson and Mattsson 1983, Jonson et al 1988, Börjesson et al 1993, Shakeshaft and Lillicrap 1993, Börjesson et al 1995, O'Meara et al 1997. Table 3 summarizes some elements, which have been subjected to in vivo XRF.…”
Section: Xrf and Naa In Vivomentioning
confidence: 99%